Promoting Social Action through Visual Literacy: New Pioneer & The Labor Defender in the Secondary Classroom - Jean, Rachel (Radical Teacher, 2018)
The notion of a classic education has been lost as technology continues to morph into the essential component of 21st Century and as educators also rise to the challenge of teaching the most diverse population of learners in American history. Literacy has shifted to include the vital “visual literacy”, the critical analysis of images, which in the past might have been an artistic pleasure as opposed to a fundamental educational skill. In this paper, I discuss this required change in the expectations of the English pedagogy. To encourage cross-curricular ties, I recommend that educators use the ancestors of today’s current magazine as a visual literacy genre, particularly political serials such as Labor Defender and New Pioneer to reach the high learning goals of visual literacy while strengthening cultural values and ideals of social action.